Global trends and hotspots of ChatGPT in medical research: a bibliometric and visualized study - Liu, Ling; Qu, Shenhong; Zhao, Haiyun; Kong, Lingping; Xie, Zhuzhu; Jiang, Zhichao; Zou, Pan (Frontiers in Medicine, 2024)
Objective With the rapid advancement of Chat Generative Pre-Trained Transformer (ChatGPT) in medical research, our study aimed to identify global trends and focal points in this domain. Method All publications on ChatGPT in medical research were retrieved from the Web of Science Core Collection (WoSCC) by Clarivate Analytics from January 1, 2023, to January 31, 2024. The research trends and focal points were visualized and analyzed using VOSviewer and CiteSpace. Results A total of 1,239 publications were collected and analyzed. The USA contributed the largest number of publications (458, 37.145%) with the highest total citation frequencies (2,461) and the largest H-index. Harvard University contributed the highest number of publications (33) among all full-time institutions. The Cureus Journal of Medical Science published the most ChatGPT-related research (127, 10.30%). Additionally, Wiwanitkit V contributed the majority of publications in this field (20). “Artificial Intelligence (AI) and Machine Learning (ML),” “Education and Training,” “Healthcare Applications,” and “Data Analysis and Technology” emerged as the primary clusters of keywords. These areas are predicted to remain hotspots in future research in this field. Conclusion Overall, this study signifies the interdisciplinary nature of ChatGPT research in medicine, encompassing AI and ML technologies, education and training initiatives, diverse healthcare applications, and data analysis and technology advancements. These areas are expected to remain at the forefront of future research, driving continued innovation and progress in the field of ChatGPT in medical research.